Conducive target range of breast cancer: Hypoxic tumor microenvironment - Cheng, Wen; Xiao, Xian; Liao, Yang; Cao, Qingqing; Wang, Chaoran; Li, Xiaojiang; Jia, Yingjie (Frontiers in Oncology, 2022)
Breast cancer is a kind of malignant tumor disease that poses a serious threat to human health. Its biological characteristics of rapid proliferation and delayed angiogenesis, lead to intratumoral hypoxia as a common finding in breast cancer.These hypoxic areas offer a promising opportunity to develop targeted therapies. In this article, we review important physicochemical changes and signaling pathways activated in the hypoxic microenvironment. And we indicate the direction of targeting hypoxia in immune cells, transcriptome, treatment resistance, and HIF inhibitors.